Pengaruh Aksesibilitas Terhadap Pengaruh Aksesibilitas terhadap Keputusan Peserta BPJS Kesehatan dalam Manentukan Puskesmas Ngamprah sebagai Fasilitas Kesehatan Tingkat Pertama (FKTP). - Widiastutie, Riska; Dewi, Lies Anggi Puspita (Universitas Pahlawan Tuanku Tambusai, 2025)
Accessibility plays a crucial role in influencing the selection of a Primary Healthcare Facility (FKTP) by BPJS Health participants. This study aims to examine the effect of accessibility measured through distance, travel time, availability and cost of transportation, as well as road infrastructure quality on the decision of BPJS participants in choosing Ngamprah Public Health Center as their FKTP. A quantitative method was employed using a survey approach, with questionnaires distributed to 100 respondents residing in four nearby villages: Sukatani, Ngamprah, Tanimulya, and Cilame. The sampling technique used was purposive sampling. The findings reveal a significant influence of accessibility on participants’ FKTP selection decisions. The more accessible a facility is perceived to be, the more likely it is to be chosen. These results highlight the strategic importance of improving accessibility to optimize the role of FKTPs in the primary healthcare system. This study recommends that both BPJS and public health centers consider physical and geographical factors when designing healthcare policies.